Cardiac function and muscular oxygen desaturation in sprint and endurance cohorts during the incremental bicycle ergometry - Papieviene, V.; Poderiene, K.; Trinkunas, E.; Grunovas, A.; Poderys, J. (Education. Physical training. Sport, 2014)
Research background and hypothesis. The objective of this study was to compare the velocity of changes of cardiac output and muscular oxygen desaturation during the graded exercise stress in endurance and sprint cohorts. Research methods. The subjects, 13 long distance runners and 11 sprinters, underwent a 50W increase in workload every 6 minutes and they exercised till the inability to continue the workout. The heart rate (HR), cardiac output and oxygen desaturation (StO2) in lateral head of the rectus femoral muscle were registered. Research results. The averaged values of change in cardiac output at each stage of workout were similar for both cohorts. We found statistically significantly higher velocities of changes in StO2 in the sprint cohort than in the endurance cohort. The lower physical performance abilities are typical of the sprint cohort compared to the endurance cohort but three was no difference between the averaged maximal HR values registered at the end of incremental ergometry. During the exercising with given work rate at stages which became subjectively hard, the StO2 decreased to the same smallest level. This means that the same type of change and the same smallest degree of StO2 occurs just before the inability to continue the exercising. Discussions and conclusions. The endurance cohort features a more extensive slow augmentation and greater peak values of cardiac output compared to the sprint cohort. The same type of changes and the same degree of muscular oxygen desaturation occur at the point of the inability to continue the exercising, but faster changes